Overweight and obesity in Portugal higher education students - Campos, Francisco; Abrantes, Bruno; Ferreira, Rúben; Marques, Mariana; M. L. Martins, Fernando; Melo, Ricardo; Mendes, Rui (Aurel Vlaicu University Arad, 2018)
Purpose. Overweight and obesity arise, essentially, as a consequence of the adoption of poor eating habits and sedentary lifestyles. Being the teenager a “microworld” in transformation, is intend to characterize and compare (gender) body composition parameters in Higher Education students. Methods. The characterization was performed through univariate analysis and the comparison using Mann-Whitney test, for a statistical significance level of 5% (p<0.05). Results. Female students presented less satisfactory results in Waist Circumference (WC) and Waist-Hip Ratio (WHiR), male students in Body Mass Index (BMI) and Waist-Height Ratio (WHeR), and there are statistically significant differences in 3 of the 4 parameters (WC, WHiR and WHeR). Conclusions. These results may be useful to define strategies to combat overweight and obesity, considering the characteristics of this specific population.
Keywords: obesity; students; sedentary lifestyle